2019
DOI: 10.1016/j.heliyon.2019.e02416
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of the heat transfer characteristics of water-based mango bark nanofluid flowing in a double-pipe heat exchanger

Abstract: In this study, the heat transfer characteristics of a new class of nanofluids made from mango bark was numerically simulated and studied during turbulent flow through a double pipe heat exchanger. A range of volume fractions was considered for a particle size of 100 nm. A two-phase flow was considered using the mixture model. The mixture model governing equations of continuity, momentum, energy and volume fraction were solved using the finite-volume method. The results showed an increase of the Nusselt number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…In an attempt to study bio-nanofluid characteristics, Onyiriuka et al [8] investigated the thermal characteristics of mango bark-water nanofluid in the horizontal in-tube heat exchanger. It was noted that there was an enhancement in the thermal performance of the nanofluid compared with water.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to study bio-nanofluid characteristics, Onyiriuka et al [8] investigated the thermal characteristics of mango bark-water nanofluid in the horizontal in-tube heat exchanger. It was noted that there was an enhancement in the thermal performance of the nanofluid compared with water.…”
Section: Introductionmentioning
confidence: 99%
“…Several enhancement methods are developed to increase the thermal and flow performance of heat exchangers. These modifications include swirl generators such as twisted tapes [9][10][11][12][13][14][15][16], artificial roughness in the form of corrugation [14] and ribs on the surface of duct [17], usage of fins and baffles [18], nanofluids [19][20][21], etc. Such modifications introduce the interference in the flow field which result in disturbed boundary layer, mixing of fluid elements as a result of which heat transfer is enhance.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticle diameter considered by 100 nm. Also, it was indicated that the average heat transfer coefficient trend with some specific amount Reynolds numbers [29]. Li et al [30] using a micro-channel heat sink to experimentally investigated the convective heat transfer of carbon-acetone nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been mainly focused on modifying the flow structure by changing heat transfer area, raising heat transfer surfaces, generating turbulent mixing. They have even considered making thinner boundary layers and enhance the heat transfer efficiency of the working fluid (2021) 3:722 | https://doi.org/10.1007/s42452-021-04701-6 by modifying thermophysical properties, such as discovering better thermal conductivities [29][30][31].…”
Section: Introductionmentioning
confidence: 99%